2015
DOI: 10.1088/1367-2630/17/2/023015
|View full text |Cite
|
Sign up to set email alerts
|

Resonance effects on the dynamics of dense granular beds: achieving optimal energy transfer in vibrated granular systems

Abstract: Using a combination of experimental techniques and discrete particle method simulations, we investigate the resonant behaviour of a dense, vibrated granular system. We demonstrate that a bed of particles driven by a vibrating plate may exhibit marked differences in its internal energy dependent on the specific frequency at which it is driven, even if the energy corresponding to the oscillations driving the system is held constant and the acceleration provided by the base remains consistently significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 64 publications
(83 reference statements)
1
25
2
Order By: Relevance
“…Nonetheless, significant deviation is observed only for very small (one-and two-particle) systems, which are, to the community at large, of comparatively little interest. In fact, it has previously been shown in experiments and simulations [34] that, for larger systems, the assumption v peak = 2πf g does indeed hold to a reasonable accuracy. So far, we have demonstrated that our very simple model can successfully capture the behaviors of a one-dimensional column of particles exposed to a single, discrete excitation.…”
Section: A Testing the Modelmentioning
confidence: 88%
See 2 more Smart Citations
“…Nonetheless, significant deviation is observed only for very small (one-and two-particle) systems, which are, to the community at large, of comparatively little interest. In fact, it has previously been shown in experiments and simulations [34] that, for larger systems, the assumption v peak = 2πf g does indeed hold to a reasonable accuracy. So far, we have demonstrated that our very simple model can successfully capture the behaviors of a one-dimensional column of particles exposed to a single, discrete excitation.…”
Section: A Testing the Modelmentioning
confidence: 88%
“…The parameters detailed above are chosen due to the fact that prior investigations have shown these values to produce quantitative agreement with data acquired from experimental systems [11,34], ensuring the reliability and real-world relevance of the results presented here.…”
Section: A Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental domain is bounded by six solid walls. For both particles and walls, the frictional coefficient is taken as 0.1 m = , a value which has been shown to accurately reproduce experimental results in vibrated systems using the same software employed here [70,71]. The implementation of this value of μ also adds to the generality of our results, as a number of easily available materials which are commonly used in experiment (for example glass, steel, acrylic) share a similar friction coefficient of 0.1 m~ [72].…”
Section: The Simulated Systemmentioning
confidence: 99%
“…It remains however difficult to observe grain-scale mechanisms in a dense packing of particles, to understand and interpret probing results; DEM grain-scale modeling [4] allows us to study particle contacts and motion in granular media to understand how grain-scale mechanics affects wave transmission in the material. This work contributes to the research on nonlinear behavior in granular materials by studying resonant frequencies [5][6][7][8], and uses as reference the oedometric cell experiments of Jia et al [9,10] on acoustic waves propagation in dense packing of glass beads.…”
Section: Introductionmentioning
confidence: 99%